Challenges and Opportunities for Spatial Data Infrastructure Development in Mozambique. Issue 1 (2nd January 2019) - Atumane, Ali Ahamed Puna; Cabral, Pedro
Abstract : The importance of access to spatial data for development and resource management is widely acknowledged worldwide. Unrestricted, reliable and efficient access to accurate, timely, and up-to-date spatial data may be achieved through a spatial data infrastructure. Thus, most developed countries implemented and continue to develop their spatial data infrastructure. In Africa, there is a growing number of governments committed to spatial data infrastructure development. This paper aims to contribute to initialize an spatial data infrastructure in Mozambique. We identified and characterized through a survey the government institutions producing, sharing, and using spatial data in the country to estimate their potential contribution to the development of the Mozambican spatial data infrastructure. We found 12 institutions producing 15 thematic datasets which can constitute the core of the spatial data infrastructure for Mozambique. Two government agencies have the technical skills and policies to make spatial data available to the public. Based on the possible contribution of these institutions, this paper proposes an spatial data infrastructure for Mozambique based on four pillars: i) organizational framework; ii) legal framework; iii) technical framework; and iv) accessibility.